2015
DOI: 10.1590/s0100-736x2015001000002
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Porphyromonas and Prevotella species in the oral microflora of cattle with periodontitis

Abstract: Abstratc: Bovine periodontitis is a progressive purulent infectious process associated with the presence of strictly and facultative anaerobic subgingival biofilm and epidemiologically related to soil management in large geographic areas of Brazil. This study aimed to detect species of the genera Porphyromonas and Prevotella, which occurr in periodontal pockets of cattle with lesions deeper than 5mm (n=26) and in gingival sulcus of animals considered periodontally healthy (n=25). Presence of the microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Botteon et al (1993) and Dutra et al (2000) showed the predominance of black-pigmented Bacteroides, that were both saccharolytic and non-saccharolytic in cultures of periodontal lesions ("cara-inchada") from cattle. Borsanelli et al (2015b) demonstrated that the occurrence of P. asaccharolytica, P. endodontalis, Prevotella buccae, P. intermedia, P. melaninogenica, and P. oralis was associated with bovine periodontitis using PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botteon et al (1993) and Dutra et al (2000) showed the predominance of black-pigmented Bacteroides, that were both saccharolytic and non-saccharolytic in cultures of periodontal lesions ("cara-inchada") from cattle. Borsanelli et al (2015b) demonstrated that the occurrence of P. asaccharolytica, P. endodontalis, Prevotella buccae, P. intermedia, P. melaninogenica, and P. oralis was associated with bovine periodontitis using PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of each bacterial DNA sample in sterile ultrapure water was performed firstly using the GenElute Mammalian Genomic DNA Miniprep Kit (Sigma, St. Louis, USA) according to manufacturer's instructions. In addition, specific primers were used to identify Porphyromonas asaccharolytica, Porphyromonas endodontalis, Porphyromonas gingivalis, Porphyromonas gulae, Prevotella buccae, Prevotella intermedia, Prevotella loescheii, Prevotella melaninogenica, Prevotella nigrescens, Prevotella oralis and Prevotella tannerae (Borsanelli et al, 2015b) by PCR.…”
Section: Bacterial Identification By Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…In ruminants and other animals it is known that Porphyromonas spp. is present in the periodontal pockets of animals with periodontitis (Senhorinho et al 2011, Borsanelli et al 2015b, Agostinho 2017, Campello 2017. Based on the results of the present study, it can be stated that besides being related to periodontitis, P. endodontalis and P. gulae are present in samples from healthy calves and calves with gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it can be evidenced that bovine oral microbiota is rich and diversified, composed of 395 genera or higher taxa and that microorganisms considered as potential periodontal pathogens are associated with the occurrence of periodontitis in these animals. These include several species of Porphyromonas, Prevotella, and Treponema, as well as Fusobacterium nucleatum, Fusobacterium necrophorum, and Actinomyces naeslundii (Dutra et al 2000, Borsanelli et al 2015a, 2015b, Borsanelli 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional microbiological analysis of lesions in bovine periodontitis using traditional methods of anaerobic culture, characterization and identification, it is possible to observe that approximately 80% of the microbiota of calves associated with periodontitis was composed of black pigmented colonizing bacteria when cultured in blood agar supplemented with hemin and vitamin K (Botteon et al 1993, Dutra et al 1999. With the use of molecular techniques such as polymerase chain reaction (PCR), which presents high sensitivity and specificity, several species of the genera Porphyromonas, Prevotella and Treponema (Borsanelli et al 2015a(Borsanelli et al , 2015b were identified in bovine periodontitis, considered as potential pathogens in humans, dogs, cats, sheep, and goats.…”
Section: Introductionmentioning
confidence: 99%